Towards a numerical simulation of supersonic mixing & combustion - Kamel, Mohammed; Idres, Moumen; Owis, Farouk; Hashem, Ali (LAP Lambert Academic Publishing, 2013)
The design and off-design studies of hypersonic air-breathing engines face many challenges because of the complexity of their internal flows. Mixing and combustion processes in Supersonic-Combustion Ramjet (scramjet) engines involve complicated aerothermochemical features such as interactions between shock-waves and boundary-layer, shock induced-combustion and recirculation zones. In this study, a numerical solver is developed and validated to be an efficient design tool capable of simulating these complicated flow features of supersonic combustors. The flow is solved based on the Reynolds Averaged Navier-Stocks equations (RANS), beside a chemical kinetics model for the computation the reactions finite rates. Finite-volume scheme is used where the convective fluxes are discretized by Roe’s scheme using MUSCL approach. And, the diffusive fluxes are centrally discretized. Pointimplicit Runge-Kutta method is applied for time integration. For the code validation, several test cases are to monitor the code ability to solve for the different diffusive and turbulent fluxes, and the chemical source term. In addition, the code is validated by resolving the transverse sonic injection into supersonic air flow in case of Helium injection from a flat plate, and the case of Hydrogen injection in single-strut scramjet engine. The effect of this injection technique in mixing and flame-holding is demonstrated. The results show good agreement with the previous numerical and experimental investigations. And, the numerical simulator proves its accuracy and robustness.